Government Internal Control Systems in Higher Education: Exploration of Management Principles, SWOT Models, and Solutions for Effective Management - Suratman, Suratman; Sugiyono, Sugiyono (JURNAL AL-TANZIM, 2024)
The main focus of the study is to identify obstacles in implementing the Government's Internal Control System (SPIP), primarily related to low commitment and lack of sincerity in the documentation process. This study aims to evaluate the government's internal control system at Sunan Kalijaga State Islamic University Yogyakarta. The study aims to explore relevant management principles, formulate a SWOT analysis model, and identify obstacles to managing the government's internal control system. This study used a mixed approach between qualitative and quantitative to analyze the effectiveness of SPIP. Data collection techniques include interviews, documentation studies, and questionnaire dissemination. Data were analyzed thematically for qualitative information from interviews and documentation studies, while descriptive statistical methods analyzed quantitative data from questionnaires. The results showed an increase in risk governance with a value of 4,205 in the managed and measurable category, creating an anti-corruption organizational culture. The SWOT model finds a Strengths Opportunities (SO) strategy focusing on maximizing internal strengths and exploiting external opportunities. The implication of this research is the need for leadership support to strengthen control systems, educate staff, and utilize technology to increase efficiency in documentation.